DIAGNOSTIC ACCURACY OF CHEST X-RAY IN CASES OF ACTIVE PULMONARY TUBERCULOSIS TAKING HIGH RESOLUTION COMPUTED TOMOGRAPHY (HRCT) AS GOLD STANDARD (The Research of Medical Science Review, 2025)
Introduction: Pulmonary tuberculosis continues to pose a significant global health challenge, highlighting the need for precise and readily available diagnostic tools. Chest X-ray is commonly utilized for TB screening; however, its diagnostic efficacy relative to high-resolution computed tomography (HRCT), which offers greater sensitivity, necessitates additional assessment, especially in high-burden contexts. Objective: To determine the diagnostic accuracy of Chest X-ray in cases of active pulmonary tuberculosis taking HRCT as gold standard. Methodology: This cross-sectional validation study was performed at Islamabad Diagnostic Centre over a six-month period (September 2024–March 2025). A total of 322 patients, aged 20 to 70 years, with suspected pulmonary tuberculosis were enrolled. Chest X-rays and HRCT scans were performed and analyzed by the qualified radiologists. HRCT was established as the gold standard. Data were analyzed using SPSS 25 to determine sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of chest X-ray, while accounting for confounding variables. Results: Active PTB was detected in 60.6% (n=195) of cases on HRCT, while chest X-ray identified 65.5% (n=211) as positive (table 2). Chest X-ray found to be highly sensitive (92.8%), however specificity was moderate (76.4%). Chest X-ray has shown overall diagnostic accuracy, PPV and NPV as 86.3%, 85.8% and 87.4% in diagnosis of pulmonary TB keeping HRCT as gold standard. Conclusion: The research demonstrates that chest X-ray serves as an effective first-line detection method for active pulmonary TB, exhibiting high sensitivity and moderate specificity. The diagnostic performance is affected by patient factors including smoking status, gender, and duration of symptoms. HRCT acts as a supplementary imaging technique, especially when chest X-ray results are ambiguous or in the context of early-stage disease.